التًقصير في حق المرأة لميراثها الشرعي في العصر الحديث - د. محمد علي حمزة الحضيري (Aljameai, 2022)
الملخص:تهدف هذه الدراسة إلى التعرف علي التقصير والحرمان السائد في هذا العصر لأرث المرأة واكل نصيبها ظلم واجحاف يمارس في حقها من نصيب تركتها في الارث، بل حرمانها منه من قبل اخوتها او اهلها ، يعتبر تعدي علي احكام الله وشرعه، والمنهج المتبع الوصفي التحليلي ، ولتحليل البيانات تم استخدام مناقشة الموضوع بطريقة منطقية رابطاً بين الأدلة المرتبطة بمحور الدراسة وبين مضمون الموضوع الذي يختاره الباحث فنتائج الدراسة هي التعدي علي حقوق الورثة يُعد من الأمور التي شددت فيها النصوص الشرعية بالنهي، حيث أوجبت على من يتعًدى علي هذه الحقوق العقوبة من الله سبحانه، وتوعده بالعذاب الاليم، والمهين، فمن هذه النتائج ما جعل الله تَعالي للمرأة نصيباً مقدراً في الميراث وفق العدل والمصلحة التي يعلمها الله تعالي والانصاف لها وتعزيز لمكانتها داخل المجتمع، وإن سلب حق المرأة في ميراثها الشرعي يعد جريمة ، لأنها مخالفه لأحكام الله من النصوص الشرعية التي أمر بها الله عز وجل وسنة الرسول صل الله عليه وسلم.Abstract:                                                                                                  .The Aim Of This Study Is to identify thy default and deprivation prevailing in this era of womens inheritance and tak their share of injustice and unfairness by exercising their rights of inheritance and depriving them of inheritance because of their brothers or family, And This Is A transgression Against The provisions Of God And His Law.The approach of this research is descriptive and analytical Research And For Date Analysis Was Used To Discuss The Topic In A logical Way, Linking The Evidence Related To The Studys Axis And The Content Of The Topic Chosen by The researcher.The results of the study that the infringement of the rights of the heirs is one of the matters in which The Sharia Texts Emphasized The prohibition, as it required That whoever infringes these rights be punished by God Almighty, And he threatens Him With painful And Humiliating Torment:Allah made the woman an estimated share in the inheritance in accordance with justice and the interests that Allah knows and fairness to her and strengthening her position within society.Stealing the woman’s right to her legal inheritance is a crime because it is in violation of the provisions of Allah from the legal texts that Allah commanded and the Sunnah of the Messenger, prophet Muhammad peace be upon him.